Faktor Faktor yang Berhubungan dengan Kejadian Diare pada Anak - Revanza Putra Pratama; Noor Latifah A (Calory Journal Medical Laboratory Journal, 2025)
Diarrhea remains a significant health problem among children, especially school-aged students. This study aims to identify factors associated with the occurrence of diarrhea in students. A literature review method was used by analyzing ten relevant scientific articles published within the last five years (2019–2024). Significant factors influencing diarrhea incidence include handwashing habits, environmental sanitation conditions such as availability of latrines and clean water, nutritional status, immunization, and health knowledge. The findings indicate that diarrhea prevention requires a multidimensional approach involving education on healthy behaviors, improvement of sanitation facilities, and family empowerment through nutrition and immunization. These results are expected to serve as a basis for schools, parents, and government in designing effective diarrhea prevention programs for students.